2019
DOI: 10.1017/s0956536119000105
|View full text |Cite
|
Sign up to set email alerts
|

Faceless Hierarchy at Nixtun-Ch'ich’, Peten, Guatemala

Abstract: Societies vary in how they approach the challenges of increased population, inequality, and occupational specialization. The city of Nixtun-Ch'ich’ and its satellite, T'up, in Peten, Guatemala exhibit orthogonal urban grids—a trait absent from all other known Maya cities. Such grids require extensive planning and the ability to mobilize the population. The present data suggests that Nixtun-Ch'ich’ was substantially larger than any of the surrounding settlements and was, therefore, a primate center during the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…As mentioned, the investment of resources to properly drain cities is (and creates) a public good, as are roads (Blanton and Fargher 2012:105). Like Harappa and Teotihuacan, Middle Preclassic Nixtun-Ch'ich' was “faceless”—it included no images of kings and the overall theme of its symbolism was cosmogenesis and fertility (Pugh et al 2020; Rice 2015:31, 2018; Rice and Pugh 2021). Absent imagery of rulers, we know little about political organization at the city.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned, the investment of resources to properly drain cities is (and creates) a public good, as are roads (Blanton and Fargher 2012:105). Like Harappa and Teotihuacan, Middle Preclassic Nixtun-Ch'ich' was “faceless”—it included no images of kings and the overall theme of its symbolism was cosmogenesis and fertility (Pugh et al 2020; Rice 2015:31, 2018; Rice and Pugh 2021). Absent imagery of rulers, we know little about political organization at the city.…”
Section: Discussionmentioning
confidence: 99%
“…The new map indicated that Nixtun-Ch'ich' differs from most Maya settlements in that it was arranged in an orthogonal urban grid (Figures 1 and 2; Pugh and Rice 2017; Pugh et al 2020; Rice and Pugh 2021). The grid, which facilitated movement as well as drainage within the city, was established in the Middle Preclassic (800–400/300 b.c. )…”
Section: Nixtun-ch'ich’mentioning
confidence: 97%
See 1 more Smart Citation
“…Soon after the beginnings of sedentary life, such formations were evidenced in the Gulf Coast, where large stone portrait heads of the powerful stood in central communities (Pool 2012). In other cases, leadership was more faceless, collective and operated with fewer elite trappings both in life or death (Carballo 2016;Pugh et al 2020). Nevertheless, across the Mesoamerican world at this time, central places, larger than surrounding settlements, emerged coincident with or shortly following the advent of sedentary life.…”
Section: Agriculture and Communities In Mesoamericamentioning
confidence: 99%
“…2000-1000 BC). At these head towns, a diverse array of spaces and nonresidential structures were defined and built that served to coordinate the community population and often the residents of smaller subsidiary settlements as well (Pool 2012;Pugh et al 2020). In the Maya lowlands, early in the Formative, raised civic-ceremonial spaces may have preceded the construction of permanent residences (Inomata et al 2019).…”
Section: The Complex Articulation Of Authority and Political Power In...mentioning
confidence: 99%